PRE-SERVICE ENGLISH TEACHERS’ PERCEPTIONS OF THE EFFECTIVENESS OF USING THE GIZMO APPLICATION TO ENRICH ENGLISH VOCABULARY - Nur Hapsi Harahap; Maryati Salmiah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Vocabulary is a fundamental component of language learning and is essential for developing effective communication skills. This study investigates the perceptions of pre-service English teachers regarding the effectiveness of the Gizmo application as a tool for enriching English vocabulary. Utilizing a descriptive qualitative approach, data were collected from 10 pre-service teachers in an English education program through the use of questionnaires and structured interviews. The results of the questionnaire were analyzed using descriptive statistics, while the interview data were analyzed using thematic analysis. Findings reveal four main themes: (1) Gizmo effectively enriches students’ vocabulary by providing exposure to new and contextualized vocabulary, (2) it serves as a medium that fits students' individual learning needs, especially due to its flexibility and personalized vocabulary input, (3) the application offers interactive, fun, and helpful features such as quizzes and repetition that motivate learners, and (4) it increases learners’ interest and confidence in using English vocabulary. Most participants expressed ingness in using Gizmo in their future teaching practices, while one participant felt the app was too basic for advanced learners. The study demonstrates that Gizmo has the potential to be a valuable digital tool in English language teaching, particularly in vocabulary enrichment. These findings are expected to provide valuable insights for educators, teacher trainers, and developers of language learning technologies, particularly in the context of mobile-assisted language learning (MALL).